Matinya Keaktifan Siswa Di Kelas Akibat Pengaruh Dari “Guru Killer” - Syauqi Hafizh Dano Ali; Lukman Ali Arsyadi (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
This study aimed to investigate the impact or influence of authoritarian and critical teacher behavior and teaching on students in the classroom, or in popular language better known by the public as the "Guru Killer". The research method used surveys and observations of interactions between teachers and students. The results show that teachers' judgmental and oppressive teaching style can significantly inhibit students' participation and reduce or even kill their activeness in the learning process. The implications of this research highlight the importance of a supportive, collaborative and empowering teaching style to create a conducive learning environment, thus achieving the set learning objectives.